Asset Securitization, Securitization Recourse, and Information Uncertainty - Cheng, Mei; Dhaliwal, Dan S.; Neamtiu, Monica (The Accounting Review, 2011)
ABSTRACT: In this study, we examine some of the consequences of asset securitization. Specifically, using a sample of bank holding companies, we investigate whether the difficulty in assessing the true extent of risk transfer, between securitizing banks and investors in asset-backed securities, affects bank information uncertainty. We find that when market participants have a greater difficulty in estimating risk transfer, banks face greater information uncertainty (i.e., larger bid-ask spreads and analyst forecast dispersion). In addition, we find that this effect is mitigated for banks that operate in a higher quality information environment. We also find that banks that securitize financial assets have higher spreads and analyst forecast dispersion as compared to non-securitizing banks.